2013
DOI: 10.1186/1471-2164-14-581
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breed and tissue compartment on the response of pig macrophages to lipopolysaccharide

Abstract: BackgroundThe draft genome of the domestic pig (Sus scrofa) has recently been published permitting refined analysis of the transcriptome. Pig breeds have been reported to differ in their resistance to infectious disease. In this study we examine whether there are corresponding differences in gene expression in innate immune cellsResultsWe demonstrate that macrophages can be harvested from three different compartments of the pig (lungs, blood and bone-marrow), cryopreserved and subsequently recovered and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
6
49
1
Order By: Relevance
“…The greater expression of genes encoding TGFB1 , which plays a key role in alveolar homeostasis , and the C‐type lectin MRC1 , which is also highly expressed in porcine AMs , is supportive of a predominantly M2 (alternatively activated) phenotype in equine AMs, which may play a role in suppressing spontaneous and/or over‐exuberant inflammation in the lung . By contrast, the highly expressed transcripts identified in PMs may reflect either a classical [M1] ( CXCL1 , CXCL3 , IL1A , IL1B , IL8 , NFKB2 ) or an alternative [M2] ( CCL22 , IL4R , IL10 ) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The greater expression of genes encoding TGFB1 , which plays a key role in alveolar homeostasis , and the C‐type lectin MRC1 , which is also highly expressed in porcine AMs , is supportive of a predominantly M2 (alternatively activated) phenotype in equine AMs, which may play a role in suppressing spontaneous and/or over‐exuberant inflammation in the lung . By contrast, the highly expressed transcripts identified in PMs may reflect either a classical [M1] ( CXCL1 , CXCL3 , IL1A , IL1B , IL8 , NFKB2 ) or an alternative [M2] ( CCL22 , IL4R , IL10 ) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous CCl 4 and ozone exposure studies in rats, the experimental exposures and sample collections were all done in one laboratory under identical conditions. Göttingen mini pigs were chosen as a clinically relevant species, resembling humans in various functions as assessed by cardiovascular, respiratory, and biochemical parameters [10, 17, 18]. In addition, the use of larger animals as an LPS model of oxidative stress allowed their use as an internal control prior to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response includes activation of free radical-generating enzymes in various types of cells that initiate host lipid peroxidation. In this study, LPS treatment of Göttingen mini pigs was chosen as a model of oxidative stress because the response of pig macrophages to LPS more closely resembles that of humans than mice in their set of macrophage-expressed systemic manifestations and LPS-inducible genes [10]. Therefore, the similarities between pigs and humans support the use of the pig as a more predictive model than the rodent in research studies [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study performed on five breeds of pig; Duroc, Píetrain, Landrace, Hampshire and Large White, found that the number of genes differentially expressed between these breeds in response to in vitro lipopolysaccharide was relatively small but included the immune-related genes Interleukin 12A (IL12A) and Colony Stimulating Factor 2 (CSF2) which were more abundantly expressed in Hampshire than Large White or Píetrain (Kapetanovic et al, 2013). In this latter study macrophage gene expression was also assessed with an Affymetrix Snowball Porcine Array, covering the entire transcriptome (Freeman et al, 2012).…”
Section: Molecular Biomarkers In Pigsmentioning
confidence: 99%